Orthodontically Induced External Apical Root Resorption in Class II Malocclusion. (22nd December 2021) - Karnati, Praveen Kumar Reddy; Seth, Priyank; Zamzuri, Ahmad Termizi Bin; Tharwani, Payal
Abstract : Orthodontic-induced external apical root resorption is one of the idiopathic phenomena as an effect, with force generated through mechanotherapy as the cause and the biological tissues with their diversified variations as witness. It is also classified as iatrogenic as a result of indeterminate application of orthodontic forces with subconscious appreciation of the existing underlying conditions. Numerous factors were identified to relate to this irreversible pathologic condition, but none were proven scientifically. Genetics and salivary markers have proved the reliability with time, but the application became insignificant limiting mostly to the research field. Different assessment methods were also identified to clinically diagnose it both subjectively and objectively. Mostly, it is identified through routine radiographic stage records like orthopantomogram or certain prediction radiographs for root resorption probability assessment like in this case. This case report discusses one such encounter which was experienced after stage 1 and 2 mechanics involving quite a few teeth. Considering the biotype of the individual and tooth morphology, the ongoing treatment was terminated and recovery measures were briefed to uplift the self-esteem of the individual. Furthermore, the prognosis is compromised to be very poor with unpredictability to any other treatment modalities.